Hubungan Pengetahuan dan Sikap Perawat dengan Penatalaksanaan Pembidaian Pasien Fraktur di RS X Sulawesi Tenggara - Nina Nurnaningsih; I Wayan Romantika; Diah Indriastuti (Holistic Nursing and Health Science, 2021)
Introduction: Fracture management is performed by splinting to immobilize the part of the body that is fractured by using a device that aims to reduce and eliminate pain, prevent movement of the fracture that can cause damage to the surrounding soft tissue. The pilot study showed that nurses’ knowledge was not related with attitude in managing patients with fractures. This study aims to determine the relationship between knowledge and attitudes of nurses and the management splint of fracture patients in the emergency room, Southeast Sulawesi Province in 2020. Methods: The study was conducted using a cross sectional design method. The population were 34 nurses in a emergency room at Hospital X Southeast Sulawesi Province. A total of 34 samples were taken by total sampling. Results: The results showed that most of the respondents had good knowledge (50.0%), most of the respondents had good attitudes (88.2%). There was a strong relationship between knowledge and the management of fracture patients (p value = 0.001 and p = 0.569), there was a strong relationship between attitude and the management of fracture patients (p value = 0.000 and p = 0.622). Conclusion: Researchers suggest to nurses in emergency room always improving their knowledge, education, skills and maintain motivation in providing emergency services to patients who have fractures.